Pharmacological efficacy of Aloe vera in wound healing: a narrative review: Eficacia farmacológica del Aloe vera en la cicatrización de heridas: una revisión narrativa - Aparicio Salcedo, Sandra Viviana (2023)
Aloe Vera has different therapeutic effects, including wound healing. The aim of this review is to determine the potential efficacy of topical use of Aloe Vera in skin wound healing. A bibliographic search of preclinical and clinical studies from 1999 to 2020 was carried out, which included the therapeutic use of Aloe vera in the healing of: burns, surgical wounds, lactation disorders, anal fissure and anal fistula; in the databases of the VHL Regional Portal, PubMed and Google Scholar. It was obtained that the topical administration of Aloe vera was effective in the healing of the mentioned wounds by mainly increasing epithelialization and collagen content. In conclusion, the properties and pharmacological presentation, chemical components and the effectiveness of Aloe vera to reduce the time of wound healing, make this plant a great therapeutic alternative. Key words: Aloe vera, wound healing, burns, surgical wounds, fissure in ano. (source: MeSH NLM)